Efficiency of lowest-unmatched price auctions - Eichberger, Jürgen; Vinogradov, Dmitri V. (Economics letters, 2016)
In Lowest-Unmatched Price Auctions (LUPA) all participants pay a bidding fee and the lowest bid placed by only one participant wins. Many LUPAs do not specify what happens with the item on offer if there is no unmatched bid. The item may remain with the auctioneer which may appear unfair given that the auctioneer collects the bidding fees. We show that in a symmetric Nash equilibrium of a LUPA with known prize both players and the auctioneer will have an expected profit of zero. Moreover, LUPAs may be seen as a value-revealing mechanism.
Gesehen am 05.05.2020